2021
DOI: 10.17517/ksutfd.798173
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Preschool Children with Down Syndrome

Abstract: Vitamin D is a fat-soluble secosteroid prohormone that is produced on the skin by contact with sunlight. Through various metabolic changes in the body, it transforms into a hormone known as calcitriol, with a key role in the calcium and phosphate metabolism (1). Vitamin D serves plenty of functions in the body. Therefore, its deficiency may cause musculoskeletal symptoms such as bone pain, muscle weakness, gait difficulty, skeletal deformity, in addition to extraskeletal symptoms such as autoimmune diseases, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…According to the preliminary results of our VD study, the DS group had a higher level of VD insufficient amounts compared to the controls. This result is consistent with a prior investigation that revealed a substantial prevalence of VD deficiency in Down syndrome children [16,17,19,20]. According to study by Stagi et al, there is a very high frequency of VD insufficiency in DS children, with a mean VD level of 14.34 ± 8.31 [21].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…According to the preliminary results of our VD study, the DS group had a higher level of VD insufficient amounts compared to the controls. This result is consistent with a prior investigation that revealed a substantial prevalence of VD deficiency in Down syndrome children [16,17,19,20]. According to study by Stagi et al, there is a very high frequency of VD insufficiency in DS children, with a mean VD level of 14.34 ± 8.31 [21].…”
Section: Resultssupporting
confidence: 92%
“…This study demonstrated a significant difference in age, BMI, milk intake, sun exposure, and meat consumption between the DS and control groups stratified by VD categories. A study in Turkey demonstrated that the VD levels significantly down from infancy until preschool in DS children [19]. Meat consumption status in children with Down syndrome is also linked to numerous nutritional issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation